Concept of Reference Diagnostics as the Foundation for Developing Diagnostic Algorithm to Support Doctor’s Decision-Making - M. A. Yakushin; A. V. Vorobeva; M. D. Vasiliev; A. P. Kudrin; T. I. Yakushina; O. Yu. Arseenkova (Здоровье мегаполиса, 2023)
The article analyzes current conceptual approaches to developing algorithms for supporting doctor's decision-making process. The need for application of sorting algorithms to generate decision-supporting algorithms is explained. We suggest a concept of reference diagnostics based on systematization of topical and nosological series that determine the direction and sequence of diagnostic process. According to the concept, each possible pathological region localization and each disease are presented as a set of positive and negative reference signs. In order to demonstrate the sequence of diagnostic algorithm elaboration, a specific neurological pathology is used as an example. The prospects for the practical application of reference diagnostics in clinical medicine are defined.